Further evaluation of modified‐bolus‐placement methods during initial treatment of pediatric feeding disorders. Issue 1 (3rd August 2020) - Ibañez, Vivian F.; Peters, Kerri P.; St Paul, Jovanie A.; Vollmer, Timothy R.
Abstract : Children with feeding disorders might pack or expel food when they lack the oral‐motor skills, the motivation, or both, to swallow. Bolus placement directly on the tongue with a Nuk (e.g., Milnes et al., 2019) or flipped spoon (e.g., Sharp et al., 2010) is a treatment that researchers generally implement after such behavior emerges (e.g., Girolami et al., 2007). However, Wilkins et al. (2014) tested the relative efficacy of Nuk presentation and upright‐spoon presentation during initial treatment of pediatric feeding disorders. In the current study, we compared the effects of (a) upright‐spoon presentation; (b) Nuk presentation; and (c) flipped‐spoon presentation on two product measures of swallowing: 15‐ and 30‐s mouth clean, and expulsion during the initial treatment of feeding disorders with 5 children. We also monitored lip closure during bite presentation and following bolus placement. Nuk presentation produced the highest levels of mouth clean and the lowest rates of expels relative to upright‐spoon presentation and flipped‐spoon presentation. We discuss potential reasons why modified‐bolus‐placement methods improved feeding behavior and how measures of oral‐motor skills might predict its necessity during initial treatment.